Collagen scaffolds reinforced with biomimetic composite nano-sized carbonate-substituted hydroxyapatite crystals and shaped by rapid prototyping to contain internal microchannels. - Sachlos, E; Gotora, D; Czernuszka, J (2006)
The next generation of tissue engineering scaffolds will be made to accommodate blood vessels and nutrient channels to support cell survival deep in the interior of the scaffolds. To this end, we have developed a method that incorporates microchannels to permit the flow of nutrient-rich media through collagen-based scaffolds. The scaffold matrix comprises nano-sized carbonate-substituted hydroxyapatite (HA) crystals internally precipitated in collagen fibers. The scaffold therefore mimics many of the features found in bone. A biomimetic precipitation technique is used whereby a collagen membrane separates reservoirs of calcium and phosphate solutions. The collision of calcium and phosphate ions diffusing from opposite directions results in the precipitation of mineral within the collagen membrane. Transmission electron microscopy analysis showed the dimension of the mineral crystals to be approximately 180 x 80 x 20 nm, indicating that the crystals reside in the intermicrofibril gaps. Electron diffraction indicated that the mineral was in the HA phase, and infrared spectroscopy confirmed type A carbonate substitution. The collagen-HA membrane is then used to make 3-dimensional (3D) scaffolds: the membrane is shredded and mixed in an aqueous-based collagen dispersion and processed using the critical point drying method. Adjusting the pH of the dispersion to 5.0 before mixing the composite component preserved the nano-sized carbonate-substituted HA crystals. Branching and interconnecting microchannels in the interior of the scaffolds are made with a sacrificial mold manufactured by using a 3D wax printer. The 3D wax printer has been modified to print the mold from biocompatible materials. Appropriately sized microchannels within collagen-HA scaffolds brings us closer to fulfilling the mass transport requirements for osteogenic cells living deep within the scaffold.